Influence of Engineered Microorganisms on Vermicomposting of Pre-processed Vegetable Waste - Palaniappan, Senthilkumar; Alagappan, Murugappan (International Journal of Engineering and Technology, 2018)
The low optimum level of vermi pile depth (10 cm-15 cm) warrants encroachment of large land area and consume more time in the vermicomposting process.  In engineered vermicomposting, the acceleration of digestion of high volume of waste was done by eliminating the pre-composting and introducing pre-processing the waste.  This process involves chopping, pulverizing, stocking, and drying the waste followed by injecting the engineered microorganisms (EM) at various depths in vermi bin during the vermicomposting process. Pre-processing and injection of EM enabled to increase the substrate depth by two-to-three-fold (30 cm).  Experimentation was conducted in five vermi bins with same quantity of worms (100 gms of E. fetida in each bin), with different stock loads of EM  (0.3ml, 0.4ml, 0.5ml, 0.6ml and 0.7ml) named as Bin 1, Bin 2, Bin 3, Bin 4 and Bin 5 respectively.  In parallel, a control (Bin C1) and conventional (Bin C2) vermi bin were also set up to compare the differences observed.  The outcome of the study clearly showed that the bin loaded with 0.7ml EM (Bin 5) stock achieved high volume reduction (70%). Moreover, the trail unit loaded with 0.5ml of EM stock (Bin 3) exhibited high biomass growth rate than its counter trail units.